IN DEFENSE OF JUVENILES SENTENCED TO LIFE legal representation and juvenile criminal justice. - Kokkalera, Stuti S. ([S.l.] : ROUTLEDGE, 2022)
This book examines how attorneys enable a meaningful opportunity for release for individuals sentenced to life as juveniles. The work provides a detailed overview of how legal representation facilitates opportunities for release for juveniles sentenced to life: juvenile lifers. It contributes to the broader literature on the importance of legal representation in the criminal legal system by investigating the role of an attorney in the parole process. Drawing on interviews with lawyers and qualitative content analyses of attorney participation in parole recordings from one state, the study illustrates how attorney assistance provides an important due process protection in the highly discretionary context of parole. The analysis of attorney representation is situated in the history of how they became prominent in the criminal legal system, and how their assistance has been viewed as vital in the parole process. Prior criminological and legal research relates the impact a lawyer can have by preparing a juvenile lifer candidate to present a suitable narrative for release, one that relates their diminished criminal culpability and rehabilitative efforts to prepare for life beyond prison. The work will be relevant to students, academics, and policy makers, particularly for state parole boards, public defender agencies, and legislatures. While the analysis is based on the experience of one state, the findings are generalizable to other states and countries that similarly conduct parole board hearings for not just their juvenile populations but also adults.
OCLC-licensed vendor bibliographic record.
Keywords: LAW / General; LAW / Child Advocacy; LAW / Comparative; Legal assistance to juvenile delinquents -- United States; Life imprisonment -- United States; Juvenile parole -- United States